BIODEGRADABLE NANOMATERIALS FOR TISSUE ENGINEERING AND REGENERATIVE MEDICINE APPLICATIONS - Fitriani Fitriani; Khalid Al Ansari; Sarah Al Sabih (Yayasan Adra Karima Hubbi, 2026)
The field of tissue engineering and regenerative medicine has seen significant advancements with the use of nanomaterials, particularly biodegradable nanomaterials, which offer promising solutions for tissue regeneration and repair. These materials, due to their biocompatibility, biodegradability, and ability to mimic the extracellular matrix, play a crucial role in supporting cell growth, tissue development, and healing processes. Despite these promising properties, challenges remain regarding the optimization of nanomaterial performance, including controlled degradation rates and tissue-specific responses. This study aims to explore the potential of biodegradable nanomaterials in tissue engineering and regenerative medicine, focusing on their applications, properties, and functional enhancements through design optimization. The research aims to evaluate the efficacy of these nanomaterials in promoting tissue regeneration in various models, including bone, cartilage, and soft tissues. The study involves the synthesis and characterization of biodegradable nanomaterials, including nanofibers, nanoparticles, and hydrogels. In vitro cell culture assays and in vivo animal models are used to assess cell viability, proliferation, differentiation, and tissue regeneration potential. The study demonstrates that biodegradable nanomaterials significantly promote cell proliferation and differentiation, accelerating tissue repair and regeneration in all tested models. Controlled degradation rates of the nanomaterials contributed to sustained cell support and tissue integration. Biodegradable nanomaterials hold substantial promise for advancing tissue engineering and regenerative medicine, offering effective and sustainable solutions for tissue repair and regeneration.